Influence of cold atmospheric-pressure-plasma in combination with different pretreatment methods on the pull-off tensile load in two-piece abutment-crowns: an in-vitro study - Carolin-Isabel Görgen; Kawe Sagheb; Karl Martin Lehmann; Irene Schmidtmann; Stefan Wentaschek (BMC, 2023)
Abstract Background In implant prosthetic dentistry, the adhesive connection of individualized ceramic crowns and prefabricated titanium bases leads to several benefits. However, the durability of the bonding could be a weak point and especially depends on sufficient surface pretreatment. Cold atmospheric-pressure plasma (CAP) is a pretreatment method that should improve the surface properties without physical damage. Thus, the purpose of this study was to investigate the influence of CAP treatment on pull-off tensile load in two-piece abutment crowns. Methods Eighty zirconia crowns and titanium bases were divided into eight groups (n = 10) according to their surface pretreatment prior to cementation with Panavia V5: no treatment (A); sandblasting (B); 10-MDP primer (C); sandblasting and primer (D); CAP (AP); sandblasting and CAP (BP); CAP and primer (CP); sandblasting, CAP and primer (DP). The specimens were thermocycled (5°/55°, 5000 cycles), and then the pull-off tensile load (TL) was measured. Statistical analyses were performed using three-way ANOVA with Tukey post-hoc and Fisher's exact tests. Results The results showed that the TL was highest in group D (p < 0.0001). Some combinations of different treatments led to effects that were greater than the sum of the individual effects. These effects were modified by interactions. Only in combination with primer, CAP treatment had a small but positive significant effect (group CP vs. C and CP vs. AP, p < 0.0001) which however did not come close to the strong interaction effect that resulted from the combination of sandblasting and primer. Conclusion Within the limitations of this study, CAP treatment cannot be recommended in this specific field of indication due to its unreliable influence on TL in combination with other pretreatment methods.